(untitled) (Global Journal of Human-Social Science, 2023)
This subject deals with a category of artifacts here the Museum which served or accompanied the enterprise of conquest-colonization of Algeria and the process of putting into a museum a people and a territory The examination is considered from the perspective of a French historiography The Museum is taken as keystone or fossil director which confirms and authenticates the French colonial project in its successive dismemberments as argued by Arnauld Le Brusq The colonial museum is placed at the first plan of an archeology of colonial France because the museum turns out to be consubstantial with the colonial project